2021
DOI: 10.1017/s0950268821000443
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus–Leptospira coinfections in small mammals from central Germany

Abstract: European orthohantaviruses (Puumala orthohantavirus (PUUV); Dobrava-Belgrade orthohantavirus (DOBV), genotype Kurkino; Tula orthohantavirus (TULV)), and Leptospira spp. are small mammal-associated zoonotic pathogens that cause diseases with potentially similar symptoms in humans. We investigated the frequency of Leptospira spp. and hantavirus single and double infections in small mammals from 22 sites in Thuringia, central Germany, during 2017. TULV infections were detected at 18 of 22 sites (mean prevalence 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 45 publications
(76 reference statements)
3
32
2
Order By: Relevance
“…Leptospira spp. are also considered as small mammal-associated zoonotic pathogens causing diseases with potentially similar symptoms in humans [ 4 ]. It is considered as one of the most important re-emerging health threats to humans by the World Organisation for Animal Health [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leptospira spp. are also considered as small mammal-associated zoonotic pathogens causing diseases with potentially similar symptoms in humans [ 4 ]. It is considered as one of the most important re-emerging health threats to humans by the World Organisation for Animal Health [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human infections by Leptospira spp. and orthohantaviruses are almost indistinguishable in their clinical presentation [ 32 ] and can often be confused with each other [ 4 ]. In addition, coinfections with orthohantaviruses are frequently observed at sites where the prevalence of Leptospira spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence ranges from 5.3% in The Netherlands [ 45 ], 7.3% in Austria [ 46 ], 10.4% in Corsica, France [ 47 ], 3.1–12% in Czech Republic [ 48 ], 7.9–12% in Spain [ 49 , 50 ] and up to 21.5% in Croatia [ 51 ]. In Germany, a mean prevalence of 6% up to 21.3% in rodents of different genera was detected [ 52 , 53 , 54 , 55 , 56 ]. Studies including multiple rodent genera concluded that rodents of the genus Microtus , as the main reservoir of Leptospira , showed much higher Leptospira prevalences (up to over 30%) compared to bank voles (4–11%) [ 52 , 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, a mean prevalence of 6% up to 21.3% in rodents of different genera was detected [ 52 , 53 , 54 , 55 , 56 ]. Studies including multiple rodent genera concluded that rodents of the genus Microtus , as the main reservoir of Leptospira , showed much higher Leptospira prevalences (up to over 30%) compared to bank voles (4–11%) [ 52 , 57 , 58 ]. Further, it is commonly assumed that Leptospira species or serovars are adapted to certain host species, e.g., L. interrogans serovar Icterohaemorrhagiae is often associated with Norway rats ( Rattus norvegicus ) [ 59 ] or L. kirschneri with field voles ( Microtus agrestis ) and common voles ( Microtus arvalis ) [ 54 ].…”
Section: Introductionmentioning
confidence: 99%